2021
DOI: 10.1097/qco.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic therapy in central venous catheter-related bloodstream infection due to Gram-negative bacilli

Abstract: Purpose of reviewThe aim of this study was to review recent data evaluating the duration of antibiotic therapy in central venous catheter-related bloodstream infection (CRBSI) due to Gram-negative bacilli (GNB).Recent findings CRBSI is the most common complication associated with the use of intravascular catheters. CRBSI directly contributes to increase additional days of hospitalization, morbidity and therefore economic costs. The incidence of GNB CRBSI has been increasing considerably in the last years; this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Previous studies have found that older patients have a higher risk for CRBSI than younger patients 40 . This result was consistent with our result.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies have found that older patients have a higher risk for CRBSI than younger patients 40 . This result was consistent with our result.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have found that older patients have a higher risk for CRBSI than younger patients. 40 This result was consistent with our result. Long hospital stays, underlying diseases such as neurological disorders, and solid organ transplantation associated with a higher risk of CRBSI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main findings of studies analysing the impact of short courses of antibiotic therapy in GNB CRBSI are depicted in Table 3. We could conclude than current available data support that a short course of antibiotic therapy must be as effective as long-course therapy for GNB-CRBSI, once the CVC has been removed [33].…”
Section: Duration Of Directed Antimicrobial Antibiotherapy After Cath...mentioning
confidence: 81%
“…Enterobacterales species are the predominant etiological agents of Gram-negative BSI, followed by Acinetobacter baumannii-calcoaceticus complex (ABC) and Pseudomonas aeruginosa [ 3 , 4 ] The ideal duration of treatment for Gram-negative bacteria remains undefined, especially in infections caused by multidrug resistant (MDR) pathogens. Guidelines recommend from 7 to 14 days of treatment for Gram-negative BSI, leaving shorter- or longer-term therapies to clinical discretion [ 5 , 6 , 7 ]. Recently, a consensus guidance recommended 7 days of therapy for uncomplicated Gram-negative BSI [ 8 ].…”
Section: Introductionmentioning
confidence: 99%